Illegal Drugs: A Review of Content on the Journalistic Treatment Given to the Subject in Three Colombian Newspapers - Acevedo Moreno, Elvia Elena (Folios, revista de la Facultad de Comunicaciones y Filología, 2013)
Media, in addition to proposing the agenda of issues on which society turns its interest, exercises influence on what to think on these same issues. Therefore the importance of studying what their messages are and how they’re constructed. This article examines the press coverage of illegal drug information published by the Colombian newspapers El Tiempo, El Espectador and El Colombiano during three circumstantial periods. The results show that the construction of the information does not allow us to evidence the complexity of the phenomenon of drugs or the wide range of views about them. Due to the fact of low depth on the journalistic genres used, the short diversity of sources (number, type and views), the limited initiative to address their own issues, among other things, it was observed, in general terms, a poor and very similar coverage to those media has given to other matters, as evidenced by at least two researches herein referenced.